Nilai-Nilai Pendidikan dalam Novel Rumah Tanpa Jendela Karya Asma Nadia: Tinjauan Sosiologi Sastra dan Implementasinya dalam Pembelajaran Sastra di SMA - Rahmawati, Nila, Dr. Nafron Hasyim (2016)
Nila Rahmawati, A310120237. Indonesian Language Education, School of Teacher Training and Education, Muhammadiyah University of Surakarta, 2016. The aims of the study are (1) to describe the structure of Asma Nadia's novel "Rumah Tanpa Jendela",(2) educational values of "Rumah Tanpa Jendela", (3) implementation of the result towards literature learning in Senior High School. This study was analyzed qualitatively as a method of the study. The object of this study is educational values of "Rumah Tanpa Jendela" by Asma Nadia. Data used were in the form of words, phrases, sentences, and paragraphs in the novel "Rumah Tanpa Jendela" which is written by Asma Nadia. The primary source is the novel of "Rumah Tanpa Jendela" by Asma Nadia which is published by Kompas Media Nusantara, in the year 2011 in Jakarta, and the thick of the novel is 180 pages. The secondary source of this research is the relevant articles. The techniques of collecting data used were scrutinize technique and writing technique. Triangulation theory was used to examine the validity of the data. The technique of analyzing data of this study was dialectical data analysis. Based on the structural analysis, the theme of Rumah Tanpa Jendela novel by Asma Nadia is a simple dream of a child. The dream comes into Rara as the main character that wants to have a window in her house. The plot of Rumah Tanpa Jendela novel by Asma Nadia is mixed or progress and flashback. The characters were analyzed namely: Rara, Aldo, Akbar, Yati, Rafi, Ms.Alia, Deni, Rara's Mother, Raga, Simbok, Bude Asih, Aldo's grandmother, Adam, Andini, Billy, Ratna, Syafri. The setting of this novel is setting of place, setting of time, and social setting. The educational values of novel Rumah Tanpa Jendela by Asma Nadia are religion value, moral value, social value, and aesthetical value. The result of the study can be implemented to teach literature in Senior High School, based on basic competence 7.2 that is analyzing intrinsic and extrinsic elements of Indonesian novel or translation novel. Keywords : Rumah Tanpa Jendela, educational values, literature learning